Livelihoods and land management in the Ioba Province in south-western Burkina Faso - Katrin Gleisberg-Gerber (University of Bonn, Center for Development Research (ZEF), 2012)
In Burkina Faso, policies influencing land management are bound to have deep impacts on the environment and on the livelihood of the rural population. Two such policies are the national program of gestion de terroirs villageois and the support programs for cotton cultivation by the private sector and the national government. This paper provides insights on the current livelihoods of rural households, identifies the key determinants of their livelihoods and categorizes them into household types. This is necessary to then analyze the impacts of the aforementioned policies on land management strategies of the different household types. The analysis includes the impacts of agricultural intensification and expansion on livelihoods as both have influenced the distribution of livelihood assets. The working paper uses data collected across three representative villages in the Ioba Province in south-western Burkina Faso in 2006/2007. It shows that poorer farm households are excluded from institutions that provide access to resources and have only limited means to employ agricultural practices to maintain soil fertility. The study indicates that differences in the land management of household types lead to differences in social and environmental outcomes. In other words, the livelihood strategies of the observed households vary. However, livelihood outcomes in the study area are rather homogenous. The homogeneity of the livelihood outcomes makes it difficult to categorize households into different types. One reason for this result might be that it is not enough to look at data that cover only one production year. Another reason is that farm households in the study region compensate limitations in one livelihood asset through a stronger focus on livelihood strategies that generate other assets.
Keywords: 330; Burkina Faso; livelihoods; land management; household categorization; household description